Control over phase separation and nucleation using a laser-tweezing potential - Walton, Finlay; Wynne, Klaas (Nature chemistry, 2018)
Control over the nucleation of new phases is highly desirable but elusive. Even though there is a long history of crystallization engineering by varying physicochemical parameters, controlling which polymorph crystallizes or whether a molecule crystallizes or forms an amorphous precipitate is still a poorly understood practice. Although there are now numerous examples of control using laser-induced nucleation, the absence of physical understanding is preventing progress. Here we show that the proximity of a liquid–liquid critical point or the corresponding binodal line can be used by a laser-tweezing potential to induce concentration gradients. A simple theoretical model shows that the stored electromagnetic energy of the laser beam produces a free-energy potential that forces phase separation or triggers the nucleation of a new phase. Experiments in a liquid mixture using a low-power laser diode confirm the effect. Phase separation and nucleation using a laser-tweezing potential explains the physics behind non-photochemical laser-induced nucleation and suggests new ways of manipulating matter. A low-power laser can cause phase separation or trigger the nucleation of a new phase in the proximity of a liquid–liquid critical point, or binodal, using a laser tweezing potential. This effect explains the physics behind non-photochemical laser-induced nucleation and suggests new ways of manipulating matter.